Conducta Suicida y Factores de Riesgo en Pacientes del Hospital Isidro Ayora de Loja, 2022 - Espinosa Castillo, Cinthya Nicole (2022)
Suicidal behavior is one of the social phenomena that has aroused most interest in recent years, it has been linked to human beings since the beginning of time, generating not only physical affectations, but also psychological sequels both to the individual who attempts to take his own life and to the people around him, its definition and conception has evolved through time. As a result, this research was developed with the purpose of determining the relationship between suicidal behavior and risk factors. For this reason, a descriptive correlational and cross-sectional design was carried out with the participation of 71 patients from the Isidro Ayora Hospital in the city of Loja, who were selected by means of an intentional nonprobabilistic sample. It was used a socioeconomic and demographic survey as instruments, Beck's suicidal ideation scale and Plutchik's suicidal risk scale. The results obtained showed that there is a statistically significant relationship between suicidal risk and age and previous suicide attempts. At the same time, there was a relationship between previous suicide attempts and: affective disorders and number of times; as for the prevalence of suicidal behavior, the medium and high levels of suicidal ideation and risk were the most predominant, besides most of the population had a previous suicide attempt; on the other hand, it was also found that marital status, age, mental disorder and the number of times of previous attempts influence suicidal behavior